2023
DOI: 10.1007/s00125-023-05905-8
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1R agonists demonstrate potential to treat Wolfram syndrome in human preclinical models

Abstract: Aims/hypothesis Wolfram syndrome is a rare autosomal recessive disorder caused by pathogenic variants in the WFS1 gene. It is characterised by insulin-dependent diabetes mellitus, optic nerve atrophy, diabetes insipidus, hearing loss and neurodegeneration. Considering the unmet treatment need for this orphan disease, this study aimed to evaluate the therapeutic potential of glucagon-like peptide 1 receptor (GLP-1R) agonists under wolframin (WFS1) deficiency with a particular focus on human beta c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, it is also associated with a number of neurological complications and psychiatric manifestations. Several studies have proven ER stress-mediated death of beta cells in WS, and therapeutic potential for diabetes medications such as glucagon-like peptide 1 receptor agonists [17, 44, 45]. In contrast, the disease mechanisms underlying the neurological and psychiatric manifestations of WS are less well understood, and recently oligodendrocytes have gotten increased attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also associated with a number of neurological complications and psychiatric manifestations. Several studies have proven ER stress-mediated death of beta cells in WS, and therapeutic potential for diabetes medications such as glucagon-like peptide 1 receptor agonists [17, 44, 45]. In contrast, the disease mechanisms underlying the neurological and psychiatric manifestations of WS are less well understood, and recently oligodendrocytes have gotten increased attention.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, until today, research has mainly focused on the diabetic phenotype of WS and the aforementioned WFS1 functions have mostly been studied in the islets of Langerhans and ý-cells of the pancreas [17, 26]. However, diabetes has become a chronic illness that can be managed via drug therapy and only has a limited impact on the quality of life of Wolfram patients.…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism seems to be the modulation of the dysregulated ER stress signaling that occurs in WS1 [ 3 ]. Other studies have demonstrated that exenatide and dulaglutide improved β-cell function by improving mitochondrial function, reducing oxidative stress, and preventing apoptosis in preclinical models of WS1 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 , 63 ] The use of iPSC‐derived human islet‐like aggregates constitutes a useful and disease‐relevant alternative to human islets to perform in vitro studies in diabetes. [ 64 , 65 , 66 ] However, some genetic manipulations are particularly inefficient in these cells such as plasmid‐mediated protein overexpression and gene silencing of very low expressed gene targets, as is the case for lncRNAs. [ 63 , 67 ] In the context of this manuscript, the technical issues associated with the genetic manipulation of iPSC‐derived human islet‐like aggregates impeded the validation of some results obtained in EndoC‐ β H1cells, pointing to the future need to fine tune these in vitro approaches and to develop novel techniques to efficiently modify the expression of low abundance non‐coding transcripts.…”
Section: Discussionmentioning
confidence: 99%